2022
DOI: 10.3390/ijerph19031267
|View full text |Cite
|
Sign up to set email alerts
|

Teleworking, Work Engagement, and Intention to Quit during the COVID-19 Pandemic: Same Storm, Different Boats?

Abstract: The ability to retain and engage employees is now, more than ever, a major strategic issue for organizations in the context of a pandemic paired with a persistent labor shortage. To this end, teleworking is among the work organization conditions that merit consideration. The purpose of this cross-sectional study is to examine the direct and indirect effects of teleworking on work engagement and intention to quit, as well as the potential moderating effect of organizational and individual characteristics on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 94 publications
(152 reference statements)
6
17
1
Order By: Relevance
“…Compared with other dimensions, the results suggested that only the dimension of UOE could play a significant mediating role between BPNS and academic engagement. The finding was in line with a study more recently carried out by Parent-Lamarche (2022) . Based on a sample of 254 Canadian employees from 18 small and medium organizations during the COVID-19 pandemic, Parent-Lamarche (2022) found that except for skill utilization and recognition, use of emotion could appear to be key considerations for organizations that wish to increase work engagement and decrease intention to quit.…”
Section: Discussionsupporting
confidence: 93%
“…Compared with other dimensions, the results suggested that only the dimension of UOE could play a significant mediating role between BPNS and academic engagement. The finding was in line with a study more recently carried out by Parent-Lamarche (2022) . Based on a sample of 254 Canadian employees from 18 small and medium organizations during the COVID-19 pandemic, Parent-Lamarche (2022) found that except for skill utilization and recognition, use of emotion could appear to be key considerations for organizations that wish to increase work engagement and decrease intention to quit.…”
Section: Discussionsupporting
confidence: 93%
“…The obtained results have not supported hypothesis 1. Therefore, teleworking was not significantly associated with job performance, which is not consistent with research that showed the association between teleworking and job performance during the first lockdown (Parent-Lamarche and Boulet, 2021b;Parent-Lamarche, 2022), as well as between teleworking and work engagement and intention to quit. Probably other organizational factors are more significant than teleworking in times of crisis, such as leadership style, and organizational support during the crisis.…”
Section: Discussioncontrasting
confidence: 80%
“… 28 Another study carried out among employees of small and medium organizations during the second and third waves of the pandemic found, on the contrary, that teleworking was detrimental, as it was associated with lower work engagement. 29 A study reported that starting teleworking from home was associated with increased psychological distress among 15,454 Japanese workers. 30 It is possible that working from home can reduce the risk of infection linked to COVID-19, particularly for health care workers.…”
Section: Theoretical Modelmentioning
confidence: 99%